Seasonality of Leaf and Fig Production in Ficus squamosa, a Fig Tree with Seeds Dispersed by Water - Pothasin, Pornwiwan; Compton, Stephen G.; Wangpakapattanawong, Prasit (PloS one, 2016)
The phenology of plants reflects selection generated by seasonal climatic factors and interactions with other plants and animals, within constraints imposed by their phylogenetic history. Fig trees (Ficus) need to produce figs year-round to support their short-lived fig wasp pollinators, but this requirement is partially de-coupled in dioecious species, where female trees only develop seeds, not pollinator offspring. This allows female trees to concentrate seed production at more favorable times of the year. Ficus squamosa is a riparian species whose dispersal is mainly by water, rather than animals. Seeds can float and travel in long distances. We recorded the leaf and reproductive phenology of 174 individuals for three years in Chiang Mai, Northern Thailand. New leaves were produced throughout the year. Fig production occurred year-round, but with large seasonal variations that correlated with temperature and rainfall. Female and male trees initiated maximal fig crops at different times, with production in female trees confined mainly to the rainy season and male figs concentrating fig production in the preceding months, but also often bearing figs continually. Ficus squamosa concentrates seed production by female plants at times when water levels are high, favouring dispersal by water, and asynchronous flowering within male trees allow fig wasps to cycle there, providing them with potential benefits by maintaining pollinators for times when female figs become available to pollinate.